Analisis Faktor-Faktor Risiko Kejadian Katarak di Daerah Pesisir Kendari - Alfi Laila; Ilyas Raupong; Juminten Saimin (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2017)
ABSTRACTBackground:Cataract is a condition where lens that usually clear and transparent become cloudy. Based on the last report, cataract is responsible for 51% of blindness that happen in the world, which presented around 20 millions people. In Indonesia, the estimate of incindent rate of cataract is 0.1% a year which means every year there is one person a new patient of cataract among 1000 people.  The occurrence of cataract cannot be separated from the risk factors that affect it. Purposes:This research aims to determine the risk factor of the occurrence of cataract in costal area of kendari. Methods:This research is observational analytic research with case-control matching design. The population were all patients who visited the Puskesmas Abeli, Nambo dan Mata in 2015-2016. The sampling method is purposive sampling with the cases are those patient who was diagnosed with cataract and the control are not. The samples are 62 people with the comparison cases and controls is 1:1 so that the number of cases-samples are 31 people and controls-samples are 31 people who had been matched such as age and gender. The instrument of this research is questionnaire. Data were analyzed by determining the odds ratio. Results:The result of this research showed that job, income, and education are a risk factor for the occurrence of cataract which have meaningful statistically. Smoking habit and drink alcohol are a risk factor for the occurrence of cataract which doesn’t have meaningful statistically. The result of bivariat test for job is OR:2.908(CI95%:1.031-8.204), income OR:3.067 (CI95%:1.053-8.934), education OR:3.431 (OR95%:1.100-10.704), smoking OR:1.816 (IC95%: 0.616-5.355) and alcohol OR:2.467 (IC95%:0.733-8.369) Conclusions:The conclusions of this research is that job, income and education is a meaningful risk factor for the occurrence of cataract. Smoking and alcohol is a meaningless risk factor in costal area of Kendari. Keywords: cataract, risk factor